If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-3x + -5) + -1(x + 2) = 44 Reorder the terms: 6(-5 + -3x) + -1(x + 2) = 44 (-5 * 6 + -3x * 6) + -1(x + 2) = 44 (-30 + -18x) + -1(x + 2) = 44 Reorder the terms: -30 + -18x + -1(2 + x) = 44 -30 + -18x + (2 * -1 + x * -1) = 44 -30 + -18x + (-2 + -1x) = 44 Reorder the terms: -30 + -2 + -18x + -1x = 44 Combine like terms: -30 + -2 = -32 -32 + -18x + -1x = 44 Combine like terms: -18x + -1x = -19x -32 + -19x = 44 Solving -32 + -19x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -19x = 44 + 32 Combine like terms: -32 + 32 = 0 0 + -19x = 44 + 32 -19x = 44 + 32 Combine like terms: 44 + 32 = 76 -19x = 76 Divide each side by '-19'. x = -4 Simplifying x = -4
| 325+6.44t=2500 | | h(t)=-16t^2+39t | | 5y=18x+.2 | | x^2+16x+21=0 | | 7x+4-2x+9= | | A=l*b | | X-5y=-15 | | 3x=8+17 | | 6x=15+x | | 2x+3x=14 | | -0.8r-6=-30 | | 2=-4+x | | (10)=-4x+5 | | 2x+a=20 | | -0.66a+3=11 | | 16y-4x=-8 | | -54=6x-18 | | 4.2k+3=-5.4 | | 3x-5=2(3+x) | | 1.2t+6=-1.2 | | gm=r | | 32y^2-18y^2= | | y=2xp-2p+1 | | 3x+10=82 | | x^3+x^2-36x+42=0 | | 2z-3i-1=0 | | 9(x-3)=7 | | 10=-4x+5 | | 5+7x=-44 | | x^2+300000=100x | | 4x-1=11x-52 | | 2(x+3)=4x+12 |